ANOMALY OF CERTAINTY AND UTILIZATION IN THE GOVERNMENT-SOE COOPERATION SCHEME ON INFRASTRUCTURE DEVELOPMENT - Andriani Latania Triramdhani, Nia Kurniati (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Infrastructure development is the driving wheel of the economy and is also the spearhead of national development. However, efforts to encourage the acceleration of infrastructure development have a very fundamental weakness namely dependence on the availability of funding for infrastructure projects.Referring to the awareness of the capital requirements, in order to achieve the target of the implementation of infrastructure projects, the Government has launched infrastructure development using the mechanism of Public-Private Partnership (PPP).Based on the PPP scheme, the Government is not in an absolute position to conduct financing through the State Budget and Expenditure Budget, but the funding can come from business entities that are cooperating with the Government.The implementation of infrastructure development that has been formally limited, namely economic infrastructure and social infrastructure. In this study, the object of study is directed explicitly at infrastructure development proposed by SOEs. However, in general, researchers try to conduct a critical study of the legality of the Assignment Letter given to State-Owned Enterprises (SOEs) by the Government directly to carry out the construction of the infrastructure. The problem that arises from the Task Letter is the emergence of anomalous legal norms from relevant laws and regulations. This research was conducted using the normative juridical method using a conceptual approach and a critical approach based on secondary data through library research.